LITERATURE REVIEW: THE EFFECT OF ACCOUNTING INFORMATION SYSTEMS ON THE PERFORMANCE OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) - Dewi, Ni Putu Runi Antika; Dananjaya, I Gusti Ngurah Agung (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study examines the effect of Accounting Information Systems (AIS) on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The research addresses the question of whether AIS implementation and utilization can enhance MSMEs performance. A literature review approach with a qualitative descriptive method was applied, analyzing nine national scientific articles published between 2016 and 2025 that were systematically selected. The results indicate that six studies found AIS to have a significant positive effect on MSMEs performance, particularly in improving financial records, report preparation, and decision-making. In contrast, three studies reported no significant impact, largely due to limited human resources, lack of accounting knowledge, and inadequate technological facilities. These findings highlight that the effectiveness of AIS depends on the readiness of MSMEs in terms of skills, resources, and technology adoption. The study implies that strengthening accounting literacy, enhancing information technology capacity, and providing government support and infrastructure are essential to optimize AIS implementation across MSMEs sectors.